1997
DOI: 10.1021/jf970057d
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Distribution of Limonin, Limonoate A-Ring Monolactone, and Naringin in the Fruit Tissues of Three Varieties of Citrus paradisi

Abstract: Limonin and naringin are the two major bitter compounds in Citrus paradisi (grapefruit), and tissuespecific patterns of their distribution are well-established. This study was undertaken to determine the distribution of these compounds within Duncan, Marsh, and Thompson Pink tissues using threedimensional fruit dissection (600-900 samples per fruit) and highly specific radioimmunoassays for limonin and naringin quantification. Results from a GLM ANOVA showed that there was no radial distribution pattern of lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…[1] Naturally, limonin in all citrus fruit tissues [22] and the amounts are varied greatly depending on the variety and part of the fruit. [23,24] Limonin content in lime residues was observed to be higher than that reported in Citrus changshanensis. Sun et al [16] found 796, 578, 3520 mg=g dry basis (ppm) of limonin contents in flavodo, albedo, and segment of Citrus hangshanensis.…”
Section: Effect Of Blanching On Chemical Compositionsmentioning
confidence: 86%
“…[1] Naturally, limonin in all citrus fruit tissues [22] and the amounts are varied greatly depending on the variety and part of the fruit. [23,24] Limonin content in lime residues was observed to be higher than that reported in Citrus changshanensis. Sun et al [16] found 796, 578, 3520 mg=g dry basis (ppm) of limonin contents in flavodo, albedo, and segment of Citrus hangshanensis.…”
Section: Effect Of Blanching On Chemical Compositionsmentioning
confidence: 86%
“…Equivalent data are also available for many other citrus species and hybrids. The chromatographic profiles of the intact glycosides can be used for identifying the botanical origin of the fruit and products such as juices, preserves and honey, and as a monitor of adulteration 3–6. Flavanone glucosides are comparatively rare but are found in some species of Mentha used as culinary herbs (0.3–3.3 g kg −1 dry weight (DW)) (where they occur as 7‐glucosides)7 and as minor components of grapefruit, lemon and sweet orange (where they occur as 4′‐glucosides) 3.…”
Section: Occurrence and Transformation During Processingmentioning
confidence: 99%
“…However, the distribution is very non‐uniform, with much higher concentrations in the solid tissues compared with the juice. For example, the naringin content of grapefruit juice was reported as 295–377 mg l −1 , whereas the albedo, back membrane and side membranes of the fruit contained 13–16, 18–27 and 11.5–17.6 g kg −1 respectively, tending to be higher towards the centre of the fruit 5. Citrus peels (albedo + flavedo) are also particularly rich, with grapefruit peel containing naringin (1–16 g kg −1 fresh weight (FW)), sour orange peel containing neohesperidin (0.7–31 g kg −1 FW) and sweet orange peel containing hesperidin (4.6–12.8 g kg −1 ) 13.…”
Section: Occurrence and Transformation During Processingmentioning
confidence: 99%
“…Fruit tissues contain limonin, especially in the juice vesicles. In other tissues limonin is present as the A‐ring monolactone ( McIntosh & Mansell, 1997). When the juice is extracted, limonate A‐ring lactone gradually converts to limonin under acidic conditions ( Hasegawa et al ., 1992 ) and, because of this development of bitter taste, the quality of juice is adversely affected.…”
Section: Introductionmentioning
confidence: 99%